Determining the effect of tung biodiesel on thermodynamic, thermoeconomic, and exergoeconomic analyses at high engine speeds - Şanlı, Bengi; Güven, Onur; Özcanlı, Mustafa; Uludamar, Erinç (Frontiers in Energy Research, 2024)
Tung biodiesel is a promising alternative fuel type produced from the tung tree. In the current study, the effect of the addition of 20%, by volume, of tung biodiesel to diesel fuel was evaluated in terms of energetic–exergetic analyses based on the first and second laws of thermodynamic at various high engine speeds (2,400, 2,600, and 2,800 rpm). Additionally, this study aimed to assess the thermoeconomic and exergoeconomic aspects of a diesel engine. The findings revealed that the amount of energy converted to useful work for the diesel fuel was higher than that of the DTB20 fuel, even though the fuel energy obtained from DTB20 fuel was higher than that of diesel fuel at all engine speeds. The highest energy and exergy efficiencies for the engine fueled with diesel fuel were obtained as 31.07% and 29.15% respectively, while the corresponding values for the engine fueled with DTB20 fuel were determined as 27.15% and 25.19% at the engine speed of 2,400 rpm, respectively. However, at 2,800 rpm, a significant decrease in both the energy and exergy efficiencies was observed for both diesel and tung biodiesel blended fuels due to the increased mechanical friction of the engine components. Furthermore, at the highest engine speed, entropy generation increased, owing to a higher exergy destruction rate. The entropy generation rate increased to 0.38 kW/K for diesel fuel and 0.46 kW/K for DTB20 fuel since the enhancement of the engine speed caused the ascent of the fuel consumption rate. Regarding thermoeconomic–exergoeconomic analyses, for both diesel and tung biodiesel blended fuels, there is no distinct difference in the thermoeconomic–exergoeconomic parameters at 2,400 and 2,600 rpm as the values of these parameters at the engine speed of 2,800 rpm increased significantly. In light of all the findings, it can be concluded that the engine speed of 2,800 rpm is not applicable to run the engine due to higher friction and corresponding energy destruction in the engine system.